2015
DOI: 10.1177/0956462415584488
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infection screening uptake and knowledge of sexually transmitted infection symptoms among female sex workers participating in a community randomised trial in Peru

Abstract: This study aims to evaluate condom use, STI screening, and knowledge of STI symptoms among female sex workers (FSW) in Peru associated with sex work venue and a community randomized trial of STI control. One component of the Peru PREVEN intervention conducted mobile-team outreach to FSW to reduce STIs and increase condom use and access to government clinics for STI screening and evaluation. Prevalence ratios were calculated using multivariate Poisson regression models with robust standard errors, clustering by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Also significant in this study was town location, compared to FSW in Kampala, residing in Arua was associated with a decrease of 33% in the likelihood of syphilis screening but an increase of 28% in the likelihood of HIV screening. Location is described in literature to influence access to and utilization of services [30, 46]. The differences in service organization (service providers, timing and costs), socio-economic and demographic characteristics could partly explain the differences in screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…Also significant in this study was town location, compared to FSW in Kampala, residing in Arua was associated with a decrease of 33% in the likelihood of syphilis screening but an increase of 28% in the likelihood of HIV screening. Location is described in literature to influence access to and utilization of services [30, 46]. The differences in service organization (service providers, timing and costs), socio-economic and demographic characteristics could partly explain the differences in screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, peer educators were used to improve awareness of CT and NG infection and healthcare service availability, which improved the uptake of testing [ 24 ]. Additionally, a community randomized trial and a cross-sectional study both conducted in Peru found that FSWs who had received prevention messages in HIV/STI health education or counseling sessions in outreach programs were more likely to seek health health services including CT and NG testing [ 25 , 26 ]. A study in the Netherlands explored the determinants of reluctance to seek CT and NG testing and found that one-third of FSWs were unaware of the possibility of getting a free and anonymous test at local STI clinics [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In similitude with this observation, a community randomized trial regarding knowledge of STI symptoms among female sex workers in Peru showed the baseline knowledge of FSWs to be 90.6%. 9 Another study conducted by R. Hemalatha et al among female sex workers in Andhra Pradesh showed that nearly 90% of FCSWs had heard of STIs and could correctly identify at least two of the most common STI symptoms. 10 The knowledge about STDs and its prevention and benefits of condom was imparted mainly through peer educators of targeted intervention where sex workers were enrolled.…”
Section: Sexually Transmitted Infections (Stis) Andmentioning
confidence: 99%